Pelaksanaan Kegiatan Nasyid dan Marsanji Sebagai Upaya Peningkatan Literasi Budaya Masyarakat Desa Tanjung Medan Labuhanbatu - Budianto Bangun; Rahma Muti’ah; Mulkan Ritonga; Ridho Kurniawan; Harimansyah Harimansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Cultural Literacy is used to analyze, create, transmit information based on experience, the use of Cultural Literacy is one of the cultural drivers. Through the dedication that is presented to the village of Tanjung Medan, it can increase the cultural literacy of the community. With a predominantly Muslim area located in Labuhanbatu Regency, North Sumatra Province, the activity was carried out for 3 days starting on 22, 27 August and 05 November 2022 at the Tanjung Medan village office room, West Bilah sub-district, Labuhanbatu district, the benefits of digital literacy to improve culture nasyid and marsanji in the village of Tanjung Medan. The purpose of this community service is to increase knowledge about the culture of the village of Tanjung Medan. The implementation method in the training for cultural literacy activities consists of three stages, the first stage is a practical test, the second stage is an understanding test through pretest and post test regarding Nasyid and Marsanji training. Results from the responses of activity participants There were 0 participants 0% responses who felt unhappy carrying out the activity, 5 participants with a percentage of 25% responded quite happy. 7 participants with a percentage of 35% happy response. 8 Participants with a percentage of 40% very happy response. The conclusion that was obtained was that the nasyid and marsanji cultural training had a positive impact, especially on the people in the village of Tanjung Medan. Suggestions need to be raised again in nasyid and marsanji training to carry out regional culture in the village of Tanjung Medan.